Bridging Ecological Rationality, Embodied Emotion, and Neuroeconomics: Insights From the Somatic Marker Hypothesis - Xu, Fuming; Xiang, Peng; Huang, Long (Frontiers in Psychology, 2020)
The somatic marker hypothesis (SMH) has been utilized to demonstrate the role of emotion and somatic state in decision-making under uncertainty over the past two decades. Despite some debate, the SMH has provided not only a neurobiological framework for understanding emotion and decision-making but also a good empirical support for ecological rationality and embodied emotion. Unlike the traditional maximizing rationality and bounded satisficing rationality, the ecological rationality stresses that emotions should be brought to the decision-making process. The embodied emotion furthermore emphasizes that emotions are embodied in the body and the brain. On the other hand, behavioral decision-making has spawned many new interdisciplines, including neuroeconomics. In this case, the SMH could act as a bridge to translate the ecological rationality and the embodied emotion into emerging neuroeconomics. Thus, this mini-review article aims to propose an integrated framework for introducing ecological rationality and embodied emotion into the field of neuroeconomics by virtue of insights from the SMH.